Contribution of mast cells in irritant-induced airway epithelial barrier impairment in vitro. (October 2020) - Van Den Broucke, Sofie; Vanoirbeek, Jeroen; Alfaro-Moreno, Ernesto; Hoet, Peter
The airway epithelium is continuously exposed to environmental irritants, which can cause adverse effects such as irritant-induced asthma (IIA). Mast cells are located near airway epithelia and are able to respond to a variety of stimuli. We aimed to investigate whether mast cells influence the response of the epithelium upon irritant exposure. Two cell lines and three different seeding conditions, that is, bronchial epithelial cells (16HBE) only, 16HBE with mast cells (HMC-1's) basolaterally, and 16HBE with HMC-1's apically, were established. Upon exposure to the environmental irritants, graphene (G), graphene oxide (GO), diesel exhaust particles (DEPs) or hypochlorite (ClO − ), transepithelial electrical resistance (TEER) and paracellular flux of fluorescent-labeled dextrans were determined, along with the release of mediators. Identical experiments were conducted with the Ca 2+ ionophore ionomycin. Exposure to G and GO induced a significant and permanent decrease of approximately 70% in TEER after 3 h of exposure, whereas DEP and ClO − exposure resulted in a transient decrease of approximately 20% in TEER. This response pattern was similar in all the different seeding conditions. After 24 h of exposure, fluorescein isothiocyanate–dextran transport was 10-fold greater for G and 5-fold greater for GO in each of the tested seeding conditions, while DEP and ClO − induced no change compared to the control. Upon exposure to the irritants, 16HBE did not release thymic stromal lymphopoietin, interleukin 33 (IL-33), or IL-1α, and HMC-1 cells did not release histamine, IL-6, or IL-8. Epithelial barrier integrity upon treatment with ionomycin was not affected by the presence of HMC-1 cells. A limited amount of IL-6 and IL-8 was released by ionomycin-exposed HMC-1 cells. To conclude, we found that the studied environmental irritants do not directly or indirectly activate HMC-1 cells. These mast cells did not influence the epithelial barrier function upon environmental exposure, and thus currently do not provide additional information for the underlying mechanism of IIA.